Chosen Peoples : Being the First "Arthur Davis Memorial Lecture" delivered before the Jewish Historical Society at University College on Easter-Passover Sunday, 1918/5678 - Zangwill, Israel, 1864-1926 (Salt Lake City, UT : Project Gutenberg, 2007)
"Chosen Peoples" by Israel Zangwill is a scholarly work that falls within the genre of historical and philosophical discourse, written in the early 20th century. The text serves as the first Arthur Davis Memorial Lecture, delivered in 1918, and addresses the complex themes surrounding the Jewish notion of being a "Chosen People" while exploring its implications historically and ethically. Zangwill delves into the cultural and societal perceptions of Judaism amidst broader human history and the interplay of spiritual identity and social responsibility. In "Chosen Peoples," Zangwill begins by examining the contentious claim that Jewish people are divinely chosen, highlighting the historical grievances this notion has sparked in both Jewish and non-Jewish communities. He contemplates the evolution of Jewish identity through biblical narratives, emphasizing that the concept of being chosen does not carry connotations of superiority; rather, it implicates a profound responsibility towards universal moral principles and ethical behavior. Zangwill elucidates the dual currents of self-interest and altruism within Judaism, arguing that the essence of the Jewish mission is to serve the greater good of humanity, dispelling both notions of racial supremacy and the dangers of self-isolation. Through a critical and reflective lens, he ultimately posits that the Jewish experience transcends ethnic confines, asserting that all human beings share a collective destiny that should strive for justice and peace. (This is an automatically generated summary.)
Release date is 2007-02-19
E-text prepared by Steven desJardins, Jeannie Howse, and the Project Gutenberg Online Distributed Proofreading Team (http://www.pgdp.net)
Keywords: National characteristics, German; Jews -- Election, Doctrine of